Development of Interactive Learning Media Based on Wordwall in Science Learning at ELementary School - Wapuah; Hartono; Prasetyo, Danang (UNDIKMA, 2025)
This study aims to develop interactive learning media based on Wordwall in the subject of science for grade IV at SD Negeri Jatiwates 1 Jombang. The research method used is the ADDIE development model which includes five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 20 fourth grade students and involved design experts, material experts, media experts, and colleagues as validators. The results of validation from experts and trials on students showed that Wordwall-based learning media were included in the